CLEAR - Scleral lenses. Issue 2 (April 2021) - Barnett, Melissa; Courey, Claudine; Fadel, Daddi; Lee, Karen; Michaud, Langis; Montani, Giancarlo; van der Worp, Eef; Vincent, Stephen J.; Walker, Maria; Bilkhu, Paramdeep; Morgan, Philip B.
Abstract: Scleral lenses were the first type of contact lens, developed in the late nineteenth century to restore vision and protect the ocular surface. With the advent of rigid corneal lenses in the middle of the twentieth century and soft lenses in the 1970's, the use of scleral lenses diminished; in recent times there has been a resurgence in their use driven by advances in manufacturing and ocular imaging technology. Scleral lenses are often the only viable form of contact lens wear across a range of clinical indications and can potentially delay the need for corneal surgery. This report provides a brief historical review of scleral lenses and a detailed account of contemporary scleral lens practice including common indications and recommended terminology. Recent research on ocular surface shape is presented, in addition to a comprehensive account of modern scleral lens fitting and on-eye evaluation. A range of optical and physiological challenges associated with scleral lenses are presented, including options for the clinical management of a range of ocular conditions. Future applications which take advantage of the stability of scleral lenses are also discussed. In summary, this report presents evidence-based recommendations to optimise patient outcomes in modern scleral lens practice.